Photonic Crystal Fiber as a Robust Raman Biosensor - Khetani, Altaf (Université d'Ottawa / University of Ottawa, 2016)
This thesis focuses on the investigation and development of an integrated optical biosensor based on enhanced Raman techniques that will provide label-free detection of biomolecules. This is achieved by using hollow core photonic crystal fibers (HC-PCF), nanoparticles, or both. HC-PCF is a unique type of optical fiber, with continuous ‘channels’ of air (typically) running the entire length. The channels serve to confine electromagnetic waves in the core of the fiber, and tailor its transmission properties. Using HC-PCF as a biosensor requires development of a robust technique to fill hollow-core photonic crystal fibers. Though several groups have reported selective filling of HC-PCF’s core, the processes are cumbersome and limit the choice of liquid to avoid multimode behavior. In my Master’s thesis, I presented a simple technique to non-selectively fill all the HC-PCF channels with samples. The non-selective filling preserves the photonic bandgap property of the fiber, and yields an extremely strong interaction of light and the sample that produces considerable enhancement of the Raman signal from the analyte. Up to now, non-selective filling was accomplished through capillary action and it delivered a Raman signal enhancement of approximately 30-fold, which is not sensitive enough to detect biomolecules at the clinical level. Moreover, there were issues of reliability and reproducibility, due to evaporation, filling and coupling light into the fiber. The objective of this PhD research was to overcome these problems by developing a robust optical fiber platform based on Raman spectroscopy that can be used in a clinical setting. I initially focused on heparin, an important blood anti-coagulant that requires precise monitoring and control in patients undergoing cardiac surgery or dialysis. Since the Raman spectra of heparin-serum mixtures exhibits Raman peaks of heparin with poor signal-to-noise ratios, I concentrated on enhancing the heparin Raman signal and filtering out the spectral background of the serum to improve detection sensitivity. Reaching maximum enhancement of the Raman signal required a strong interaction of light and analyte, which can be achieved by using hollow core photonic crystal fiber as I had used in my Master’s research. Using a small piece of HC-PCF I was able to reach an enhancement in the heparin Raman signal of greater than 90-fold. With this degree of enhancement, I was able to successfully detect and monitor heparin in serum at clinical levels, something that had never been accomplished previously. After developing HC-PCF as a Raman signal enhancer, I focused on making the HC-PCF sensor robust, reliable and reusable. This was achieved by integrating the HC-PCF with a differential pressure system that allowed effective filling, draining and refilling of the samples in an HC-PCF, under identical optical conditions. To demonstrate the device’s detection capabilities, various concentrations of aqueous ethanol and isopropanol, followed by different concentrations of heparin and adenosine in serum, were successfully monitored. To further improve the sensitivity of the HC-PCF based Raman sensor, I incorporated surface enhanced Raman scattering (SERS), by introducing nanoparticles into the HC-PCF fibers. The research focused on determining the optimal volume and size of silver nanoparticles to achieve maximum enhancement of the Raman signal in the HC-PCF. The HC-PCF enhanced the Raman signal of Rhodamine 6G (R6G) approximately 90-fold. In addition, the optimal size and volume of AgNP enhanced the Raman signal of R6G approximately 40-fold, leading to a total enhancement of approximately 4,000 in HC-PCF. This was then used to demonstrate the application of a SERS based HC-PCF sensing platform in monitoring adenosine (a clinically important molecule), as well as malignant cells such as leukemia. Finally, I used hollow core crystal fibers to significantly enhance the efficiency of two-photon photochemistry. Although two-photon photochemical reactions are difficult to achieve with a small volume, I accomplished it by using a novel platform of HC-PCF to efficiently execute the two-photon induced photodecarbonylation reaction of cyclopropenone 1, and its conversion to the corresponding acetylene. The simple optical design configuration involved coupling an 800-nm tsunami laser to a short piece of HC-PCF filled with the sample. This allowed me to increase the efficiency of two-photon induced photochemistry by 80-fold, compared to a conventional spectrophotometer cuvette. Thus, this work leads to the use of HC-PCFs to more effectively study two-photon induced photochemistry processes, which was limited due to the difficulty of detecting photochemical events with a small excitation volume.
Keywords: hollow core photonic crystal fiber; biosensor; optical sensor; Raman spectroscopy; PCF; biological sensing and sensors; surface-enhanced; SERS; bandgap fiber; cell analysis; Raman scattering